Jardins partagés : une contribution habitante au système agri-alimentaire territorialisé rennais - Giulia Giacchè; Yvon Le Caro (VertigO)
This paper aims to give some evidence of the contribution of the urban community garden’s experience to the renewal of the place-based agro-food system (PAS) in the city of Rennes (Brirtanny, France). To mingle thoughts about inhabitant’s experience and about the dynamics of PAS, three theoretical backgrounds are refered to. The italian territorialist approach which twins agriculture, sustainability and the city ; socio-economic research on place-based agro-food systems and the social geography which considers community gardens as ‘espaces-enjeux’ (spatial issues). From 27 semi-structured interviews of gardeners and association leaders, a content analysis of discourses and a lexicometric analysis using the IraMuTeQ software are presented. At the individual level, ties and places are built from agricultural and food practices whereas they are motivating the commitment. At the PAS level, the process of territorialization is that the social interactions, flows and networks that are committed, more than the localism of economic channels. Lexicometric analysis points out strong linkages between individual practices and economic flows, between the garden’s places and the dynamics of associative networks, between interindividual ties and stakeholders conflictuality.